Juridical Analysis of Victims of Revenge Porn According to Law Number 44 of 2008 and Maqashid Sharia - Salma Yanita; Mutimatum Niami (Universitas Muhammadiyah Surakarta, 2024)
This research aims to juridically analyze victims of revenge porn in the context of Law Number 44 of 2008 and Maqashid Sharia. The research method used is document analysis and qualitative approach by collecting data from literature studies and related legislation. The novelty of this research lies in the approach that integrates the perspective of positive law with the principles of Maqashid Sharia, thus providing a holistic view of legal protection for victims of revenge porn. The results show that there is a gap in the legal protection of victims of revenge porn between Law Number 44/2008 and the principles of Maqashid Sharia. The legal and social implications of the gap are discussed in depth. In conclusion, legal protection for victims of revenge porn requires a holistic approach that considers aspects of positive law and sharia values. Harmonization between the two aspects is needed to ensure effective protection of revenge porn victims.